Application of econometric methods for evaluating the impact of economic factors on the long-term credit volumes - Abakumova, Juliet G.; Bely, Stanislau A. (Journal of the Belarusian State University. Economics, 2019)
The implementation of the aims of sustainable economic development in the context of financial constraints determines the need for banks to participate in the investment process. Thus, bank lending is an integral element of the modern economy, naturally acting as an object of state regulation. Using the statistical and econometric methods the influence of internal factors on the lending volume was investigated, and a model was constructed in the distributed lags of the forecast for the growth of long-term lending. The model shows that such indicators as the producer price index of industrial products, the refinancing rate, the devaluation of the national currency and the M2 monetary aggregate have a significant impact on the volume of long-term lending. The findings obtained during the study and on the basis of the model can be used by banks to develop a policy for lending to the real sector of the country’s economy, as well as by enterprises to improve their business activities.